Pemberdayaan Sekeha Teruna sebagai Kelompok Tangguh Bencana di Desa Apit Yeh Manggis Karangasem - Sulisnadewi Ni Luh Kompyang; I Wayan Candra (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2022)
Background: Poltekkes Denpasar is one of the health universities that certainly has the task and role of doing community service and its role is needed in the context of disaster mitigation and response. Community assistance and empowerment activities, especially the younger generation, can be carried out with the aim of assisting the community in the process of strengthening community potential in anticipating and facing disasters. Purpose: The purpose of this community service activity is to make the community able and aware of disasters by providing education about disasters and BHD training. Methods: Community service is carried out by providing education and training to stripling warriors as a disaster resilient group. Results: This BHD training activity improves participants' knowledge scores on basic life support. This activity is felt to be very useful by the stripling family, where they hope that they will later be able to provide first aid to people who experience respiratory arrest or cardiac arrest before health workers arrive. Handling respiratory arrest and cardiac arrest during the golden period will go a long way towards saving lives. Conclusion: Education has been carried out to the stripling of Apit Yeh Traditional Village about disaster mitigation and BHD training and there has been an increase in knowledge after being given education Keywords: Empowerment; Sekeha Teruna; Disaster Resilient